Proposing an organizational framework for the Sharīʿah Secretariat of Islamic banks in Bangladesh - Md. Kausar Alam; Abu Umar Faruq Ahmad; Aishath Muneeza; Mosab I. Tabash; Md Adnan Rahman (ISRA International Journal of Islamic Finance, 2022)
Purpose - Sharīʿah Secretariat plays a significant role in assisting Sharīʿah Supervisory Boards (SSBs) in their role in achieving Sharīʿah compliance in Islamic banks (IBs). The key objective of the study is to develop a organizational framework of the Sharīʿah Secretariat for the IBs in Bangladesh. Design/methodology/approach - The study applied qualitative case study research. The data have been collected from 17 respondents through semi-structured interviews from IBs and professional experts in Bangladesh. Findings - This study proposes a full-time Sharīʿah Secretariat and several departments for further enhancement of the Sharīʿah functions in IBs in Bangladesh. The framework proposed in this study covers the formation, functions, composition, qualification, reporting line, independence, remuneration and terms of appointment of the Sharīʿah Secretariat to set a uniform benchmark for all IBs in Bangladesh. It is anticipated that the outcomes of this research will assist to further strengthen the Sharīʿah governance of IBs in Bangladesh. Research limitations/implications - This research contributed to the national and global regulatory authorities and IBs by proposing a Sharīʿah Secretariat framework for the smooth functioning of the IBs in Bangladesh. The framework proposed in this study covers the formation, functions, composition, qualification, reporting line, independence, remuneration and terms of appointment of Sharīʿah Secretariat. Originality/value - This study proposed a framework which is considered the first organizational framework so far for the Sharīʿah Secretariat of IBs in Bangladesh. IBs can apply this proposed framework to form their Sharīʿah Secretariat structure.
Keywords: 330; Bangladesh; Islamic banks; Sharīʿah governance; Sharīʿah Secretariat